Otomatisasi Pengujian Perangkat Lunak Menggunakan Telenium pada Aplikasi Berbasis Kivy Framework - Utomo, Alim Budhi; Suprihadi, Suprihadi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
PT XYZ is a retail company that uses POS (Point of Sales) application in each of its stores to record transactions, automatic calculations, and print receipts. PT XYZ has millions of transactions every day, therefore system testing is needed to ensure that the POS application is running properly. When testing is done manually, there are often various problems such as inaccurate results due to limited human resources to a lot of time consuming because it is done repeatedly. To overcome these problems, test automation is made using Telenium which is integrated with Jenkins. This research was conducted based on the black box testing method. Input in the system in the form of a test scenario is then executed and the results will be sent via email. During testing, if an error occurs, the location of the error will be displayed in detail and sent via email by Jenkins. The results show that the application of Telenium in testing Kivy-based applications facilitates the testing process and accelerates the discovery of errors in the system so as to improve the quality of applications with a more efficient approach.